2007
DOI: 10.1007/s00104-007-1348-y
|View full text |Cite
|
Sign up to set email alerts
|

Was bringt die Minimalisierung des Zugangstraumas für den Patienten

Abstract: Minimizing the access trauma of surgical interventions is becoming an essential task in modern surgery in order to make the treatment more comfortable for the patient. Minimally invasive surgery has had a major impact on the improvement of surgical results over the last decade. This is why such surgery is often named as the third patient friendly revolution in surgery after the introduction of asepsis and anesthesia. Operations that caused a huge strain on the patients in the past and led to immense costs for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 37 publications
0
3
0
1
Order By: Relevance
“…The concept of natural orifice surgery (NOS) has changed the surgeon’s perspective; natural openings of the body are used by interdisciplinary teams to reach the target region directly, thereby causing minimal tissue trauma. The aim is to reduce collateral damage and complications and to fasten recovery of the patient [17, 26]. In our opinion, a true NOS procedure is a pure endoscopic approach through natural orifices of the body without any additional skin incisions.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of natural orifice surgery (NOS) has changed the surgeon’s perspective; natural openings of the body are used by interdisciplinary teams to reach the target region directly, thereby causing minimal tissue trauma. The aim is to reduce collateral damage and complications and to fasten recovery of the patient [17, 26]. In our opinion, a true NOS procedure is a pure endoscopic approach through natural orifices of the body without any additional skin incisions.…”
Section: Discussionmentioning
confidence: 99%
“…Morbidity and mortality rates following several surgical and oncological procedures have significantly improved during the last decades due to the advancement of surgical techniques. Especially the introduction of minimally invasive techniques resulted in many advantages for the patients, i.e., a lesser operative trauma, faster recovery, less pain, and a reduction of the ICU and hospital length of stay [ 7 ]. A randomized controlled trial (TIME trial) also confirmed the superiority of the minimally invasive approach in complex esophageal resections.…”
Section: Introductionmentioning
confidence: 99%
“… 11 13 Downsizing of incisions, trocar size, and trocar number can help decrease postoperative pain and increase postoperative quality of life. 14 Data from large case series and case registries suggest that TV hybrid NOTES cholecystectomy is safe when performed by surgeons well trained in minimally invasive techniques. 15 17 A recent systematic review and meta-analysis of TV hybrid NOTES cholecystectomy 18 supports those findings.…”
mentioning
confidence: 99%